2014
DOI: 10.1371/journal.pone.0111615
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Model for Branching Morphogenesis of Lake Cress Compound Leaf

Abstract: Lake cress, Rorippa aquatica (Brassicaceae), is a semi-aquatic plant that exhibits a variety of leaf shapes, from simple leaves to highly branched compound leaves, depending on the environment. Leaf shape can vary within a single plant, suggesting that the variation can be explained by a simple model. In order to simulate the branched structure in the compound leaves of R. aquatica, we implemented reaction-diffusion (RD) patterning onto a theoretical framework that had been developed for serration distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Therefore, the extensive knowledge on leaf development accumulated from these compound-and simple-leafed model species may help to reveal the molecular mechanism regulating heterophylly in R. aquatica. Indeed, studies on submergence tolerance in Rorippa species have been successfully performed based on comparisons with Arabidopsis (Akman et al, 2012;Sasidharan et al, 2013), and phylogenetic and modeling-based analyses have also been reported (Nakamasu et al, 2014;Nakayama et al, 2014). These features make R. aquatica an excellent model species to investigate the mechanism regulating heterophylly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the extensive knowledge on leaf development accumulated from these compound-and simple-leafed model species may help to reveal the molecular mechanism regulating heterophylly in R. aquatica. Indeed, studies on submergence tolerance in Rorippa species have been successfully performed based on comparisons with Arabidopsis (Akman et al, 2012;Sasidharan et al, 2013), and phylogenetic and modeling-based analyses have also been reported (Nakamasu et al, 2014;Nakayama et al, 2014). These features make R. aquatica an excellent model species to investigate the mechanism regulating heterophylly.…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous study (Nakamasu et al, 2014), the number of higher-orders of axes on each secondary axis were predicted to increase intermittently. For example, the n th newest secondary axis would have C n ¼ 2C nÀ2 þ C nÀ1 ðn !…”
Section: Degrees Of Asymmetry In Leaf Axes Can Be Theoretically Estimmentioning
confidence: 87%
“…In the previous model for divaricate-leaf morphogenesis (Nakamasu et al, 2014), a 1D boundary domain on a 2D plane ( ¼ leaf DEVELOPMENTAL DYNAMICS …”
Section: Asymmetric Axis Distributions Were Explained By An Equally Smentioning
confidence: 99%
See 2 more Smart Citations